2007
DOI: 10.1073/pnas.0604716104
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral insertional mutagenesis identifies RUNX genes involved in chronic myeloid leukemia disease persistence under imatinib treatment

Abstract: The kinase inhibitor imatinib mesylate targeting the oncoprotein Bcr-Abl has revolutionized the treatment of chronic myeloid leukemia (CML). However, even though imatinib successfully controls the leukemia in chronic phase, it seems not to be able to cure the disease, potentially necessitating lifelong treatment with the inhibitor under constant risk of relapse. On a molecular level, the cause of disease persistence is not well understood. Initial studies implied that innate features of primitive progenitor ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…EMT induction of transformed mammary epithelial cells leads to enrichment of cancer stem cells . Together with the report that increased RUNX3 expression is associated with cancer persistence in CML (Miething et al, 2007), it may be that RUNX3 is involved in cancer stem cell growth through modulation of EMT processes. Moreover, these findings point to the possibility that RUNX3 not only functions as a tumor suppressor during early tumor development, but may affect late stages of cancer progression.…”
Section: Molecular Mechanisms That Underlie Runx3's Anti-tumor Propermentioning
confidence: 70%
See 2 more Smart Citations
“…EMT induction of transformed mammary epithelial cells leads to enrichment of cancer stem cells . Together with the report that increased RUNX3 expression is associated with cancer persistence in CML (Miething et al, 2007), it may be that RUNX3 is involved in cancer stem cell growth through modulation of EMT processes. Moreover, these findings point to the possibility that RUNX3 not only functions as a tumor suppressor during early tumor development, but may affect late stages of cancer progression.…”
Section: Molecular Mechanisms That Underlie Runx3's Anti-tumor Propermentioning
confidence: 70%
“…As the only Runx protein expressed in this lymphoma, Runx3 thus seems to synergize with MYC oncogene to promote lymphomagenesis (Stewart et al, 2002). Miething et al (2007) further explored RUNX3's cancer function in leukemia when they incorporated a drug used for treatment of Bcr-Abl-expressing leukemia, imatinib, in their retroviral mutagenesis screen-they showed that insertion of a retroviral element in the vicinity of the RUNX3 promoter results in elevated RUNX3, which in turn led to increased resistance to imatinib-induced apoptosis and thus chronic myeloid leukemia (Miething et al, 2007). Runx3 was also identified as a cancerassociated gene by Sleeping Beauty transposable elements-transposon integration at the 5 0 position of the RUNX3 gene was associated with T-cell lymphoma (Dupuy et al, 2005) and prostate cancer (Rahrmann et al, 2009 Altogether, these findings suggest that while RUNX3 inactivation is a major determinant of cancer pathogenesis (see Table 1) and clinical outcome in many cancer types, in certain tumor types, overexpression of RUNX3 is oncogenic.…”
Section: Insertional Mutagenesis Screen Implicates Runx3 In Tumor Devmentioning
confidence: 92%
See 1 more Smart Citation
“…As BMT is a curative therapy for leukemias, the anti-tumor effect of CTLs was tested on the growth of Bcr-Abl-transformed B-ALL cells established by transformation of BM with MSCV MIG-p185 Bcr-Abl/GFPexpressing retroviral construct. 15 The Figure 7). Slightly elevated score levels in mice transplanted with TCD BM plus CTLs and L125 indicated tumor-dependent weight loss and fur ruffling.…”
Section: In Vitro-generated Alloantigen-specific Ctls Induce An Efficmentioning
confidence: 99%
“…As only 4/13 of cases with mutated RUNX1 were concomitantly mutated in BCR-ABL (Figure 1), we suggest that abnormalities in RUNX1 have an independent role in tyrosine kinase inhibitor resistance and may contribute to treatment failure. 1,8 Figure 1 Frequencies and distribution of mutations. Frequencies are given for molecular mutations in RUNX1, ASXL1, IKZF1, WT1, TET2, IDH1, NRAS, KRAS, CBL and TP53.…”
mentioning
confidence: 99%